Simultaneous Removal of Carbon, Nitrogen and Phosphorus from Domestic Wastewater by Sequencing Batch Reactor - Ho, Yun Kit (2001)
Sequencing Batch Reactor(SBR) had been found to be an alternative biological treatment for simultaneous removal of carbon, nitrogen and phosphorus from domestic wastewater. Nevertheless studies of this alternative treatment system are few in Malaysia. Thus, research has to be done to explore the potentials of such treatment in our country. A bench scale SBR with a working volume of 2L, was set up. The reactor had a stable flowrate of 1.4Ltbr maintaining a food to microorganism ratio of around 0.16 and a minimum sludge age of 6-9 days. In this study, two major operational strategies were used in achieving the best removal of the three nutrients. In the first operational strategy where different total cycle hours were applied, the 6 hour total cycle hour produced the best removal efficiency in terms of total suspended solids (TSS)[97%], biological oxygen demand (BOD)[85%), chemical oxygen demand (COD)[87%] and total Kjeldahl nitrogen (TKN)(>90%]. Nevertheless phosphorus removal seemed to be comparable with the other strategy operations, 8hr and 10hr total cycle time. The next operational strategy involved the manipulation of various ratio of aerobic and anaerobic period. Three main ratio, anaerobic:aerobic(fill:react) ratio of 1 :2.7, 1:1 and 1.7:1 were taken into consideration. Longer aerobic period (fill:react ratio 1:2.7) produced the best removal efficiency for TSS(95%), COD(89%), BOD(90%) and TKN (>90%). Total phosphate removal efficiency averaged about 38%. Hence, longer aerobic period strategy produced better overall nutrients removal efficiency. In operational strategy involving fill:react ratio, the nitrification rates ranged from 1.2 to 2.4 mg.g"l VSS day" I which were comparable to previous studies(Palis & Irvine., l985; Vuoriranta et.al.,1993; Rustrian et.al., 1998). The denitrification rates ranged from 1.2 to 3.7 mg.g-l VSS day"l which were also comparable to previous works(Palis & Irvine, 1985; Vuoriranta et.al.,1993; Bortone et.al., 1994; Rustrian et.al., 1998). The P-release rates ranged from 0.018 to 0.027 mg Pig VSS/min while P-uptake rates ranged from 0.010 to 0.024 mg Pig VSS/min.